Understanding Teacher Resilience and Students' Psychosocial Aspects in Islamic Primary Education: Evidence from a Madrasah Ibtidaiyah in Central Java - Syamsul Falah; Johan Untung; Akhmad Muzakki; Alif Firmansyah (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
This study examines the relationship between teachers' resilience levels and their understanding of students' psychosocial aspects at Madrasah Ibtidaiyah Ihsaniyah 01 Debong Tengah using a correlational quantitative approach with a sample of all teachers (n=18). The instruments used were based on the Connor & Davidson resilience scale and Mitchell's psychosocial indicators. The Cronbach's alpha reliability results for the resilience scale were 0.925, and for the psychosocial understanding scale were 0.836, indicating that the scales were reliable for use. The results showed that most teachers had moderate levels of resilience and psychosocial understanding. Pearson's correlation analysis produced a coefficient of 0.471 with a p-value = 0.049 at a 95% confidence interval, indicating a significant positive relationship between teacher resilience and students' psychosocial understanding, with teacher resilience contributing 22% to the variation in psychosocial understanding. This study emphasizes the importance of strengthening teacher resilience through training and psychological support, especially in Islamic education. Developing teacher resilience not only supports the well-being of teachers themselves but also has a positive impact on student development and well-being. ABSTRAK Penelitian ini mengkaji hubungan antara tingkat resiliensi guru dan pemahaman terhadap aspek psikososial siswa di Madrasah Ibtidaiyah Ihsaniyah 01 Debong Tengah menggunakan pendekatan kuantitatif korelasional dengan sampel seluruh guru (n=18). Instrumen yang dipakai berbasis skala resiliensi Connor & Davidson dan indikator psikososial Mitchell. Hasil reliabilitas alpha cronbach skala resiliensi sebesar 0,925 dan skala pemahaman psikososial sebesar 0,836, sehingga skala tersebut dinyatakan reliabel untuk digunakan. Hasil penelitian menunjukkan bahwa sebagian besar guru berada pada tingkat resiliensi dan pemahaman psikososial sedang. Analisis korelasi Pearson menghasilkan koefisien 0,471 dengan nilai p-value = 0,049 pada interval kepercayaan 95%, mengindikasikan hubungan positif signifikan antara resiliensi guru dan pemahaman psikososial siswa, dengan resiliensi guru memberikan kontribusi 22% terhadap variasi pemahaman psikososial. Penelitian ini menegaskan pentingnya penguatan resiliensi guru melalui pelatihan maupun dukungan psikologis khususnya pada pendidikan Islam, pengembangan resiliensi guru bukan hanya mendukung kesejahteraan guru sendiri tetapi juga berdampak positif pada perkembangan dan kesejahteraan siswa.